Legal Force of Administrative Remedies in the Settlement of State Administrative Disputes: Kekuatan Hukum Tindakan Administratif dalam Penyelesaian Sengketa Administrasi Negara - Masbait, Putri Julian; Salmon, Hendrik; Pattipawae, Dezonda R. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Indonesia, as a constitutional state, mandates that administrative actions adhere to legal norms, where administrative dispute resolution mechanisms play a vital role in ensuring justice and accountability in governance. Specific Background: The existence of administrative remedies—comprising objections and administrative appeals—serves as a non-judicial mechanism designed to resolve conflicts internally before proceeding to the State Administrative Court (PTUN). However, inconsistencies between Law No. 5/1986, Law No. 30/2014, and Supreme Court Regulation No. 6/2018 have created uncertainty regarding the obligatory nature of these remedies. Knowledge Gap: Limited research has comprehensively analyzed the binding legal force of administrative remedies and their implications for legal certainty and access to justice. Aims: This study aims to analyze the legal force and implications of administrative remedies in resolving state administrative disputes. Results: Findings show that administrative objections generally lack binding legal force and function more as recommendations, while administrative appeals possess stronger but under-implemented authority. Novelty: The research highlights disharmony among the relevant legal frameworks and its effect on the principle of exhaustion of administrative remedies. Implications: Strengthening the effectiveness and accountability of administrative remedies is crucial to enhance access to justice and ensure legal certainty within Indonesia’s administrative law system. Highlights: Examines the inconsistency between laws regulating administrative remedies. Identifies the weak binding power of objections and limited efficacy of appeals. Highlights the need for stronger accountability to ensure access to justice. Keywords: Legal Force, Administrative Remedies, State Administrative Disputes, Legal Certainty, Access to Justice